Smoking is an Independent Marker of Poor Prognosis in Cutaneous Melanoma - Kalle Mattila; Helmi Vihinen; Antti Karlsson; Heikki Minn; Pia Vihinen; Eetu Heervä (Medical Journals Sweden, 2023)
Previous studies have suggested that persistent tobacco smoking impairs survival in cutaneous melanoma, but the effects of smoking and other prognostic factors have not been described in detail. This study examined the association of smoking (persistent, former, or never) with melanoma-specific (MSS) and overall survival (OS) in patients with cutaneous melanoma treated in Southwest Finland during 2005 to 2019. Clinical characteristics were obtained from electronic health records for 1,980 patients. Smoking status was available for 1,359 patients. Patients were restaged according to the 8th edition of the tumour-node-metastasis (TNM) classification. Smoking remained an independent prognostic factor for inferior melanoma-specific survival regardless of age, sex, stage, and comorbidities. The hazard ratio of death from melanoma was 1.81 (1.27−2.58, p = 0.001) in persistent and 1.75 (1.28−2.40, p = 0.001) in former smokers compared with never smokers. In 351 stage IV patients, smoking was associated with increased melanoma-specific and overall mortality: median MSS 10.4 (6.5−14.3), 14.6 (9.1−20.1), and 14.9 (11.4−18.4) months, p = 0.01 and median OS 10.4 (6.5−14.3), 13.9 (8.6−19.2), and 14.9 (11.7−18.1) months, p = 0.01 in persistent, former, and never smokers, respectively. In conclusion, since smoking represents an independent modifiable poor prognostic factor in patients with cutaneous melanoma, smoking habits should be proactively asked about by healthcare professionals, in order to support smoking cessation.